Influence of Data and Formulas on Trust in Information from Journal Articles in an Operating Room Management Course. Issue 11 (1st June 2016) - Dexter, Franklin; Van Swol, Lyn M.
Abstract : To make good decisions, operating room (OR) managers often act autocratically after obtaining expert advice. When such advice is provided by e-mail, attachments of research articles can be included. We performed a quasi-experimental study using an evaluation of 4 articles used in a 50-hour OR management course to assess how their content influences trust in the article's content, including its quality, usefulness, and reliability. There were (a) 2 articles containing data with specific examples of application for health systems and 2 without and (b) 2 articles containing appendices of formulas and 2 without. Some of the formulas in the readings were relatively complicated (e.g., stochastic optimization using the Lagrange method) and unlikely to be used by the subjects (i.e., they show what does not need to be done). Content complexity (±data, ±formulas) served both as sources of limitation in understanding the content and potentially as peripheral cues influencing perception of the content. The 2-page evaluation forms were generated with random sequences of articles and response items. The N = 17 subjects each completed 9 items about each of the 4 articles (i.e., answered 36 questions). The 9-item assessment of trust provided a unidimensional construct (Cronbach α, 0.94). Formulas in the articles significantly increased trust in the information ( P = 0.0019). Presence of data did not significantly influence trust ( P = 0.15). Therefore, when an expert sends e-mail to a manager who has completed this basic OR management science and asks a question, choosing a paper with formulas has no disadvantage.